Cartilage. Volume 2, - Grässel, Susanne; Aszódi, Attila (Springer, 2017)
In three Volumes this mini book series presents current knowledge and new perspectives on cartilage as a specialized yet versatile tissue. This second volume is dedicated to basic pathologies of the two most common osteoarticular diseases affecting large segments of the Western population, osteoarthritis and chondrodysplasias. This book addresses Professors, researchers and PhD students who are interested in musculoskeletal and cartilage biology and pathobiology.- Resumé vydavatel
Keywords: chrupavka; patologická fyziologie; cartilage; pathological physiology; elektronické knihy; sborníky; electronic books; papers of several authors